Preliminary Study into the Marketing Mix and Target Market for Koffie Fabriek Aroma - Kesadaran, Matahari; Wandebori, Harimukti (Journal of Business and Management, 2015)
Abstract - Koffie Fabriek Aroma is a family-owned coffee business in Bandung that has been in operation for more than 80 years. Koffie Fabriek Aroma currently focuses more on market dominance strategies, operations, and human resource instead segmenting, targeting, and positioning, or analyzing weaknesses in its marketing mix. Therefore, Koffie Fabriek Aroma is limited in its marketing tactics, which relies almost solely on word-of-mouth. Although Koffie Fabriek Aroma is popular among a niche market, there are still many people who have never heard of Koffie Fabriek Aroma, especially outside of the Bandung area, so it may further expand its business by using other differentiated targeting strategies, such as online marketing. Conducting marketing mix and market segmentation analysis may help Koffie Fabriek Aroma grow by allowing it to target customers and position itself more effectively. This study aims to find the market segment for Koffie Fabriek Aroma customers in terms of demographic, geographic, behavioral, and psychographic characteristics. It also aims to analyze the effectiveness of Koffie Fabriek Aroma’s current marketing mix in terms of the 4 P’s (product, price, promotion, and place). This study uses a mixed-method design which combines aspects of both quantitative and qualitative research. Quantitative data was collected through online questionnaires, which used purposive sampling in order to collect 107 respondents age 18 and older in the Greater Bandung (which includes Cimahi, and surrounding areas) and Greater Jakarta (which includes Bogor, Depok, Tangerang, Bekasi, and surrounding areas) metropolitan areas who have heard of Koffie Fabriek Aroma. The survey was distributed online via Google Forms from 22 June 2015 to 27 July 2015. Qualitative data was collected through observations conducted at the Koffie Fabriek Aroma store on Jalan Banceuy during Monday, 18 May 2015 at 12:00 PM and Wednesday 15 July 2015 at 11:00 AM for one hour each. The results from both sources of data were analyzed and compared to see if there was a convergence of evidence that would allow strong conclusions to be made. The study concluded that there may be a significant segment of Koffie Fabriek Aroma customers among males age 40-64, and that there may be a large proportion of smokers among its customers. 79.59% of regular coffee buyers in this sample are active on social media, indicating that there may be opportunities for online marketing. In terms of marketing mix, the study concluded that Koffie Fabriek Aroma had a good product, due to its strong flavor and unique taste, and good pricing, but poor promotion and distribution, because its main store is located in an unclean and crowded area in Jalan Banceuy, and it cannot be easily purchased elsewhere.